Dans toute son exubérance : Affirmation de soi et autoreprésentation chez Caroline Monnet - Marcoux, Gabrielle (Canadian Journal of Film Studies, 2020)
In this interview, multidisciplinary artist Caroline Monnet discusses how acts of critical self-representation open up new spaces for territorial, linguistic, and identity negotiations and affirmations for Indigenous creators. In this sense, Monnet expresses her desire to put forward exuberant, strong, and diverse representations of Indigenous women in order to counter pervasive rhetorical dynamics of victimhood conveyed by mass media and cinema. As she presents some of the visual and discursive techniques she develops through her films, installations, and photographic works, Monnet reflects on the constructive dialogues – as well as the moments of incommunicability – that emerge and fade within various spaces and contexts of creation and reception. She considers that her individual and collective creative projects fall within a pivotal period of self-determination for Indigenous artists; she thus provides a critical overview of current discourses of (re)concililation.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé